Predicting the probability of falls in community-dwelling elderly individuals using the trail-walking test - Yamada, Minoru (Springer Japan, 2010)
BACKGROUND: Falling is a common problem in the fast-growing elderly population. Multitasking or engaging in two or more activities at the same time is common in daily living. OBJECTIVE: To determine the usefulness of the trail-walking test (TWT) for predicting a fall in community-dwelling elderly individuals. METHODS: This was a prospective study in which the TWT was used to evaluate the risk of falling among a group of community-dwelling elderly individuals (n = 171) with a mean age of 80.5 ± 5.6 years. The following tests were conducted: TWT, trail-making test (TMT), timed-up-and-go test (TUG), functional reach (FR) test, one-leg standing (OLS) test, and 10-m walking time test. Test–retest reliability was assessed by repeating the TWT within 2 weeks of the first trial, and there was a 1-year follow-up. Stepwise logistic regression analysis was used to analyze whether the TWT, TMT, TUG, FR, OLS, or 10-m walking tests predicted falling. RESULTS: The test–retest reliability of TWT was high (intraclass correlation coefficient 0.945, p < 0.001). Fifty-nine participants (34.5%) had reported a fall during the year preceding the 1-year follow-up. The stepwise logistic regression analysis revealed that only the TWT was significantly related to falling (odds ratio 1.160, 95% confidence interval 1.107–1.214; p < 0.001). In total, 77.8% of cases were correctly classified. CONCLUSION: When reliability and validity were considered, the TWT was most useful test of those evaluated for assessing the risk of fall among our elderly cohort.